Microfiber cloth embroidery and preparation process thereof
By introducing photosensitizer, flexibility enhancer and plasticizer into the microfiber cloth matrix, combined with silicone coating and thermal filler, the edge burrs and brittleness problems during laser processing are solved, and the texture and service life requirements of high-end products are achieved.
Patent Information
- Application Number
- CN202411927594.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the laser processing, the existing microfiber fabric matrix has poor molecular structure uniformity, resulting in obvious edge burrs and high brittleness of the material, making it difficult to meet the texture and service life requirements of high-end products.
The water-based polyurethane composition is optimized, and photosensitizers, flexibility enhancers and plasticizers are introduced to achieve controllability of material decomposition through the photochemical action of lasers, reducing burrs and brittle problems. At the same time, silicone coating is used to assist processing, and the thermally conductive filler disperses the laser heat to avoid overheating of the edges.
The laser processing edges are smooth and burr-free, which improves the pull resistance and wear resistance of the embroidery layer, extends the service life of the product, and meets the texture requirements of high-end products.
Smart Images

Figure CN119663561A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microfiber cloth embroidery preparation, in particular to a microfiber cloth embroidery and a preparation process thereof. Background Art
[0002] Microfiber fabrics are widely used in high-end clothing, luggage and home decoration due to their good softness, wear resistance and leather-like texture. Embroidery, as an important decorative technique, increases the three-dimensional sense and aesthetics of embroidery through the embroidery layer, making the combination of microfiber fabrics and embroidery a process with market potential. However, in order to meet the needs of higher-end products, the processing technology of microfiber fabric embroidery needs to be further improved, especially in the hollow embroidery process. The edge quality of the hollow area processed by laser and the stability of the embroidery layer directly determine the overall texture and service life of the product.
[0003] The microfiber cloth substrate is mostly prepared by impregnation with ordinary water-based polyurethane or solvent-based polyurethane. Although these substrates have certain flexibility and wear resistance, their molecular structure is often poorly uniform during laser processing, resulting in random laser decomposition paths and obvious edge burrs, making it difficult to meet the smooth requirements of the edges of the embroidery area. At the same time, solvent-based polyurethane will release a large amount of volatile organic compounds during the processing process, which does not meet the needs of green production. Although water-based polyurethane has improved in processing adaptability and environmental friendliness, its characteristics for laser processing are still obviously insufficient.
[0004] Existing laser processing technology usually uses single-wavelength laser to remove materials, lacking the synergistic mechanism of photochemical and thermal effects, resulting in serious heat accumulation in the thermal decomposition area during laser processing and obvious edge overburning problems. At the same time, there is a lack of effective auxiliary protection technology at the edge of the hollow area. Direct processing will lead to uneven material decomposition, forming burrs or cracks, which seriously affect the smooth progress of subsequent embroidery processes.
[0005] In view of the deficiencies in the prior art, the present invention provides a microfiber cloth embroidery product and a preparation process thereof. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a microfiber cloth embroidery and a preparation process thereof, which solves the problem that the microfiber cloth substrate is mostly prepared by impregnation with ordinary water-based polyurethane or solvent-based polyurethane. Although these substrates have certain flexibility and wear resistance, they often have poor uniformity of molecular structure during laser processing, resulting in random laser decomposition paths and obvious edge burrs.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: a microfiber cloth embroidery, comprising the following structure: A microfiber cloth substrate, wherein the microfiber cloth substrate is made of a microfiber mesh cloth impregnated with an aqueous polyurethane composition; A laser hollowed-out area, wherein the laser hollowed-out area is formed by laser processing, and the edge of the hollowed-out area is smoothed by laser processing; an embroidery layer, wherein the embroidery layer is arranged in the laser hollowed-out area and is sewn with polyester embroidery thread.
[0008] Furthermore, the microfiber cloth matrix is prepared by using an aqueous polyurethane composition, and the flexibility enhancer of the aqueous polyurethane (such as polydimethylsiloxane) can improve the tensile properties and laser processing adaptability of the material at the molecular level; after the photosensitizer is introduced, the controllable decomposition of the material is achieved through the photochemical action of the laser, reducing the generation of random cracks and burrs.
[0009] Preferably, the aqueous polyurethane composition comprises the following components: 55-65 wt.% of waterborne polyurethane, wherein the waterborne polyurethane is prepared by reacting polyether polyol, aromatic polyisocyanate and chain extender; 1-3 wt.% of photosensitizer, wherein the photosensitizer is selected from imide compounds or ultraviolet light initiators; 2-5 wt.% of flexibility enhancer, wherein the flexibility enhancer is polydimethylsiloxane; 3-6 wt.% of plasticizer, wherein the plasticizer is a citrate or a phthalate; 0.5-2 wt.% of a curing accelerator, wherein the curing accelerator is an organic tin catalyst or an amine catalyst; The solvent is 20-30 wt.%, and the solvent is a mixture of deionized water and isopropanol.
[0010] Furthermore, waterborne polyurethane (55-65 wt.%) is prepared by the reaction of polyether polyol, aromatic polyisocyanate and chain extender, wherein aromatic isocyanate provides hardness of the material and polyether polyol improves flexibility.
[0011] Photosensitizer (1-3 wt.%): such as imide compounds or ultraviolet light initiators, which can trigger photochemical cleavage after absorbing laser photons and promote directional decomposition of materials.
[0012] Flexibility enhancer (2-5 wt.%): such as polydimethylsiloxane, improves the flexibility and high temperature resistance of polyurethane.
[0013] Plasticizer (3-6 wt.%): such as citrate, which reduces the brittleness of polyurethane and improves the material adaptability in embroidery processing.
[0014] Curing accelerator (0.5-2 wt.%): such as organic tin catalyst, accelerates the cross-linking reaction of polyurethane.
[0015] Solvent (20-30wt.%): such as deionized water and isopropyl alcohol, used to disperse and adjust the fluidity of the material. The hard segment and soft segment of the waterborne polyurethane are combined to achieve a balance between mechanical properties and flexibility. The photosensitizer selectively breaks under the action of the laser, reducing the randomness of thermal decomposition during laser processing, thereby ensuring that there are no burrs on the edges. The synergistic effect of the flexibility enhancer and plasticizer further improves the material stability of embroidery processing.
[0016] Preferably, the polyester embroidery thread of the embroidery layer is formed by twisting three filaments, each filament has a diameter of 10 to 20 microns, and the tensile strength of a single polyester embroidery thread is 200 to 300 MPa.
[0017] Furthermore, the siloxane coating melts during the laser processing to form a protective layer, which reduces the scope of pyrolysis and plays a role in smoothing the edges; the thermal conductive filler disperses the laser heat and reduces the risk of overheating at the edges, thereby effectively avoiding the generation of burrs and irregular edges.
[0018] Preferably, the edge of the laser hollowed-out area is formed by auxiliary processing of a siloxane coating, the thickness of the siloxane coating is 30 to 50 microns, and the coating further comprises a thermally conductive filler, the thermally conductive filler is aluminum oxide powder or silicon oxide powder, the particle size of the thermally conductive filler is 0.5 to 1.5 microns, and the mass fraction is 10 to 15 wt.%.
[0019] Furthermore, the edge of the hollow area is assisted by coating with a siloxane coating, the coating thickness is 30 to 50 microns, and contains a thermally conductive filler (such as aluminum oxide powder or silicon oxide powder, particle size 0.5 to 1.5 microns, mass fraction 10 to 15 wt.%).
[0020] The siloxane coating melts during the laser processing to form a protective layer, which reduces the scope of pyrolysis and plays a role in smoothing the edges; the thermal conductive filler disperses the laser heat and reduces the risk of overheating at the edges, thereby effectively avoiding the generation of burrs and irregular edges.
[0021] A preparation process of microfiber cloth embroidery, a preparation process of microfiber cloth embroidery, characterized in that it comprises the following steps: Preparation of microfiber cloth substrate: impregnating microfiber mesh cloth into an aqueous polyurethane composition and drying to form a microfiber cloth substrate; Applying coating: applying a silicone coating on the surface of the microfiber cloth substrate; Laser processing: forming a hollow area on the microfiber cloth substrate by laser processing; Embroidery technology: a polyester embroidery thread embroidery layer is arranged in the hollow area, wherein the embroidery density is 15 to 30 stitches per centimeter.
[0022] Furthermore, the polyester embroidery thread is formed by twisting three strands of filaments, each strand of filament has a diameter of 10 to 20 microns, and a single embroidery thread has a tensile strength of 200 to 300 MPa. The embroidery density is 15 to 30 stitches per centimeter, the stitch spacing is 1.5 to 2.5 mm, and the minimum distance between the embroidery thread and the hollow edge is 0.3 to 0.5 mm.
[0023] The twisting of filaments improves the tensile and wear resistance of the embroidery thread, making it less likely to break during the embroidery process; the optimization of density and spacing ensures the three-dimensional effect of the embroidery layer, while avoiding direct contact between the embroidery thread and the edge, reducing wear.
[0024] Preferably, the immersion temperature of the aqueous polyurethane composition is 30-40° C., the immersion time is 3-5 minutes, the drying temperature is 60-80° C., the drying time is 30-60 minutes, and the immersion method is static immersion or cyclic immersion.
[0025] Furthermore, the microfiber mesh cloth is statically impregnated or cyclically impregnated at an impregnation temperature of 30-40° C. for 3-5 minutes; the drying temperature is controlled at 60-80° C. for 30-60 minutes.
[0026] Static or cyclic impregnation ensures that water-based polyurethane penetrates evenly into the microfiber mesh; low-temperature drying ensures that the polyurethane dispersion maintains a stable molecular arrangement structure during the curing process, thereby improving the flexibility of the matrix.
[0027] Preferably, the silicone coating is applied by spraying or roller coating, and after coating, it is cured at 60-100° C. for 20-40 minutes. An adhesion enhancer is added to the coating, and the adhesion enhancer is an acrylate copolymer, and its content is 3-5wt.% of the total mass of the coating.
[0028] Furthermore, the silicone coating is applied by spraying or roller coating, and after coating, it is cured at 60-100° C. for 20-40 minutes, and 3-5 wt. % of an adhesion enhancer (such as an acrylate copolymer) is added to the coating.
[0029] When the siloxane coating is cured at high temperature, it forms a strong interfacial bonding force with the substrate surface; the adhesion enhancer further improves the adhesion of the coating to prevent it from falling off due to thermal effects during laser processing.
[0030] Preferably, the laser processing comprises the following steps: The hollowed-out area was photochemically pretreated using a 355nm ultraviolet laser with a laser power of 0.5 to 1.0W / cm 2 , scanning speed is 200~300mm / s; The hollow area is removed using a green laser with a wavelength of 532nm and a laser power of 1.5 to 2.5W / cm 2, the scanning speed is 100-200 mm / s, and the focus diameter is controlled in the range of 100-200 microns.
[0031] Furthermore, a UV laser with a wavelength of 355 nm is used for photochemical pretreatment, and the laser power is 0.5 to 1.0 W / cm 2 , scanning speed is 200~300mm / s; Green laser with a wavelength of 532nm is used for thermal decomposition of materials, and the laser power is 1.5-2.5W / cm 2 , the focal diameter is controlled at 100 to 200 microns.
[0032] Ultraviolet laser induces the decomposition of photosensitizer to form a stable splitting path; green laser achieves precise removal of materials through local heating, while cooling the airflow (flow rate 5-10L / min, temperature -5-10°C) reduces heat accumulation and prevents burrs and thermal damage.
[0033] Preferably, the embroidery process uses polyester embroidery thread to sew in a single needle cycle mode, the stitch spacing is 1.5 to 2.5 mm, and the minimum distance between the embroidery thread and the hollow edge of the microfiber cloth is 0.3 to 0.5 mm.
[0034] Furthermore, the polyester embroidery thread is sewn in a single needle cycle mode, the stitch spacing is 1.5 to 2.5 mm, and the embroidery density is 15 to 30 stitches per centimeter.
[0035] The single-needle cycle method controls the embroidery tension to ensure the uniformity of each stitch; the stitch spacing is optimized to avoid too dense or too sparse stitches that affect the beauty and durability of the embroidery.
[0036] Preferably, during the laser processing, a cooling air flow of 5 to 10 L / min is introduced simultaneously, the cooling medium is nitrogen or carbon dioxide air flow, and the temperature of the cooling air flow is controlled between -5°C and 10°C.
[0037] The present invention provides a microfiber cloth embroidery product and a preparation process thereof, which has the following beneficial effects: 1. The present invention adopts a technical solution of optimizing the design of a waterborne polyurethane composition. By introducing a photosensitizer, a flexibility enhancer and a plasticizer into the waterborne polyurethane, the microfiber cloth substrate has excellent flexibility and wear resistance, and the directional decomposition of the material is achieved during laser processing. The technical effects of no burrs on the edge of the laser processing and resistance to pulling and abrasion during embroidery are achieved. Compared with the technical solution of only using ordinary waterborne polyurethane or organic solvent-based polyurethane to prepare the microfiber cloth substrate in the prior art, the shortcomings of many burrs on the edge and greater material brittleness after laser processing are solved.
[0038] 2. The present invention adopts a technical solution of siloxane coating assisted processing. By coating a siloxane coating containing thermal conductive fillers on the surface of the microfiber cloth substrate, the edge of the hollow area is protected during laser processing. The technical effect of smooth edges, no cracks and uniform heating of the processing area is achieved. Compared with the technical solution of directly using laser processing to form the hollow area in the prior art, the problem of crack generation and irregular shape caused by overheating of the edge is solved.
[0039] 3. The present invention adopts the technical solution of dual-wavelength laser collaborative processing technology, combining a 355nm wavelength ultraviolet laser for photochemical pretreatment and a 532nm wavelength green laser to complete thermal decomposition processing, assisted by synchronous cooling airflow control. The technical effect of controllable decomposition path at the edge of the hollow area, high processing efficiency and low thermal accumulation effect is achieved. Compared with the technical solution of single-wavelength laser processing of microfiber cloth in the prior art, it solves the shortcomings of low processing efficiency, significant thermal damage and unstable decomposition path.
[0040] 4. The present invention adopts a design scheme that optimizes polyester embroidery thread and embroidery density. By selecting high-strength polyester embroidery thread and reasonably setting the stitch spacing and embroidery density, the embroidery layer is ensured to have good pull resistance and three-dimensional sense. The technical effect of stable embroidery layer structure, excellent visual effect and long service life is achieved. Compared with the technical scheme of ordinary embroidery thread with disordered embroidery in the prior art, the shortcomings of easy deformation of the embroidery layer, serious wear of the embroidery thread and poor overall texture of the product are solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Please refer to the attached Figure 1 : Example 1: Microfiber cloth embroidery based on photosensitizer optimization and its preparation process Specific implementation steps Preparation of microfiber cloth substrate Preparation of waterborne polyurethane composition: The waterborne polyurethane composition is prepared according to the following ratio: Waterborne polyurethane: 60 wt.% (made from 60 mol.% of polyether polyol, 30 mol.% of aromatic polyisocyanate and 10 mol.% of chain extender); Photosensitizer: 2wt.% (imide compound); Flexibility enhancer: 4wt.% (polydimethylsiloxane); Plasticizer: 5wt.% (citrate); Curing accelerator: 1wt.% (dibutyltin catalyst); Solvent: 28 wt.% (mixing ratio of deionized water and isopropanol 2:1) The above components were stirred at 600 rpm for 40 minutes at room temperature until they were evenly dispersed.
[0044] Impregnation and drying: The microfiber mesh cloth was immersed in the composition at 35° C. for 4 minutes, then taken out and allowed to stand for 5 minutes to allow the surface to adhere evenly; it was then placed in an environment of 70° C. to dry for 50 minutes to obtain a microfiber cloth substrate that is flexible and suitable for laser processing.
[0045] Silicone coating Prepare coating solution: Siloxane film former: 45wt.%, thermal conductive filler (alumina powder, particle size 0.8 micron): 12wt.%, adhesion enhancer (acrylate copolymer): 4wt.%, solvent (isopropyl alcohol): 39wt.%; Stir at 500 rpm for 40 minutes.
[0046] Coating method: The spraying method is adopted, and the coating thickness is controlled at 40 microns; After coating, the coating was cured at 80°C for 30 minutes.
[0047] Laser Processing Preprocessing: Use ultraviolet laser with a wavelength of 355nm and a power of 0.8W / cm 2 , scanning speed 250mm / s, activate the photosensitizer and initiate the photochemical reaction.
[0048] Material Removal: Use green laser with wavelength of 532nm and power of 2W / cm 2 , focus diameter 150 microns, scanning speed 150mm / s, complete the hollow area processing.
[0049] cool down: A nitrogen flow of 8 L / min was introduced simultaneously, and the cooling temperature was 5°C.
[0050] Embroidery Use three-strand twisted polyester embroidery thread, with a single filament diameter of 15 microns and a tensile strength of 250 MPa; The embroidery density was set to 20 stitches per centimeter, the stitch spacing was 2 mm, and the embroidery thread was kept 0.4 mm away from the edge.
[0051] Summary of Examples This embodiment achieves smooth edge processing of the hollow area and high-strength bonding of the embroidery layer by optimizing the ratio of the photosensitizer and the laser processing technology. This technology significantly reduces the generation of burrs, improves the tensile resistance of the embroidery layer, and solves the problems of many edge burrs and severe wear of the embroidery layer in the prior art. The focus of this embodiment is on the role of the photosensitizer, combined with ultraviolet laser pretreatment, to achieve precise control of the decomposition path.
[0052] Example 2: Microfiber cloth embroidery with improved laser processing and cooling technology Specific implementation steps Microfiber cloth substrate preparation The substrate was prepared according to the same formulation and process as in Example 1.
[0053] Silicone coating The coating solution was the same as that in Example 1, but the coating thickness was adjusted to 35 μm, and the content of the thermal conductive filler (silicon oxide powder, particle size 1.0 μm) was adjusted to 10 wt.%.
[0054] Laser Processing Preprocessing: Use ultraviolet laser with a wavelength of 355nm and a power of 0.6W / cm 2 , scanning speed 280mm / s.
[0055] Material Removal: Use green laser with wavelength of 532nm and power of 2.2W / cm 2 , focus diameter 180 microns, scanning speed 120mm / s.
[0056] Dynamic Cooling: A carbon dioxide gas flow was used with a flow rate of 10 L / min and a cooling temperature of 0°C.
[0057] Embroidery Use three-strand twisted polyester embroidery thread, with a single filament diameter of 18 microns; The embroidery density is 25 stitches per centimeter and the stitch spacing is 1.8 mm.
[0058] Summary of Examples By adjusting the coating thickness and laser processing parameters, the smoothness of the edge of the hollow area was further optimized. The cooling method was changed to carbon dioxide gas flow, and the temperature was reduced to 0°C, which significantly reduced the damage to the substrate caused by heat accumulation. Compared with Example 1, the edge accuracy of the hollow area was higher and the three-dimensional sense of the embroidery layer was enhanced, but the laser processing efficiency was slightly reduced, indicating that different cooling methods have a greater impact on the stability of laser removal.
[0059] Example 3: Microfiber cloth embroidery based on high-density embroidery design Specific implementation steps Microfiber cloth substrate preparation The preparation of the substrate is the same as in Example 1.
[0060] Silicone coating The coating thickness was adjusted to 50 μm and the adhesion enhancer content was increased to 5 wt.%.
[0061] Laser Processing Preprocessing: Use ultraviolet laser with wavelength of 355nm and power of 0.7W / cm 2 , scanning speed 260mm / s.
[0062] Material Removal: Use green laser with wavelength of 532nm and power of 1.8W / cm 2 , focus diameter 150 microns, scanning speed 140mm / s.
[0063] cool down: A nitrogen flow of 7 L / min was introduced and the cooling temperature was -2°C.
[0064] Embroidery Use three-strand twisted polyester embroidery thread, with a single filament diameter of 15 microns and a tensile strength of 280MPa; The embroidery density is increased to 30 stitches per centimeter, with a stitch spacing of 1.5 mm.
[0065] Summary of Examples This embodiment increases the embroidery density and optimizes the coating adhesion, making the embroidery layer more compact and significantly improving the visual three-dimensional effect, which is suitable for high-end decorative purposes. Compared with embodiments 1 and 2, the laser power is reduced, the focal diameter is smaller, the embroidery layer is more tightly combined with the edge, and the overall durability is higher, but the processing time is slightly increased.
[0066] Example 4: Embroidery based on flexible enhanced microfiber cloth Specific implementation steps Microfiber cloth substrate preparation In the waterborne polyurethane composition, the proportion of the flexibility enhancer is increased to 5 wt.%, and the proportion of the plasticizer is reduced to 3 wt.%.
[0067] Silicone coating The coating thickness was adjusted to 30 μm and the particle size of the thermal conductive filler was 1.2 μm.
[0068] Laser Processing The laser processing parameters are the same as those in Example 1.
[0069] Embroidery Use highly flexible polyester embroidery thread with a diameter of 17 microns and a tensile strength of 240MPa; The embroidery density is 20 stitches per centimeter and the stitch spacing is 2 mm.
[0070] Summary of Examples By optimizing the flexibility enhancer, the microfiber cloth embroidery of this embodiment shows stronger flexibility, and is stable in both tensile resistance and edge smoothness of the embroidery layer. Compared with other embodiments, this embodiment is more suitable for bending and pulling scenes and is suitable for the field of clothing, but the three-dimensional sense is slightly inferior to that of embodiment 3.
[0071] Results analysis between examples Example 1 demonstrates the key role of photosensitizers, which effectively reduce burrs by inducing photochemical reactions with ultraviolet lasers; Example 2 shows the control ability of cooling method and laser parameters on edge quality, and carbon dioxide gas flow cooling is more suitable for high-precision scenarios; Example 3 emphasizes the optimization of embroidery density and adhesion enhancer for visual and functional effects, and is suitable for high-end decoration; Example 4 improves the overall flexibility and adaptability of the product by optimizing the flexibility enhancer, and is suitable for dynamic use requirements.
[0072] Comparative Example 1: Preparation of microfiber cloth substrate without adding photosensitizer Differences from Example 1 In comparative example 1, the addition of photosensitizer is eliminated, and other formulas and processes are consistent with those in example 1. This design mainly compares the key role of photosensitizer in the laser processing process to verify whether it can effectively control the material decomposition path and reduce edge burrs.
[0073] Preparation process Microfiber cloth substrate preparation: Prepare a waterborne polyurethane composition, the components are as follows: Waterborne polyurethane: 60wt.%; Flexibility enhancer: 4wt.%; Plasticizer: 5wt.%; Curing accelerator: 1wt.%; Solvent: 30 wt.% (without adding photosensitizer).
[0074] The microfiber cloth substrate was prepared according to the impregnation and drying process of Example 1.
[0075] Applying silicone coating: Coating thickness 40 microns; The coating solution composition is the same as in Example 1.
[0076] Laser Processing: The laser processing parameters are consistent with those in Example 1 (ultraviolet laser + green laser dual wavelength processing).
[0077] Embroidery craft: The embroidery density is 20 stitches per centimeter and the stitch spacing is 2 mm.
[0078] Comparative Example 2: No cooling airflow was used during laser processing Differences from Example 2 In comparative example 2, the cooling airflow during the laser processing was eliminated, and other processes were kept consistent with those of example 2. This design is mainly used to verify the effect of the cooling airflow on the laser heat accumulation and edge processing effect.
[0079] Preparation process Microfiber cloth substrate preparation: The matrix was prepared in full accordance with the formulation and process of Example 1.
[0080] Applying silicone coating: The coating thickness was adjusted to 35 microns; The coating composition is the same as in Example 2.
[0081] Laser Processing: Preprocessing: Use ultraviolet laser with wavelength of 355nm and power of 0.6W / cm 2 , scanning speed 280mm / s; Material Removal: Use green laser with wavelength of 532nm and power of 2.2W / cm 2 , scanning speed 120mm / s; No cooling air flow.
[0082] Embroidery craft: The embroidery density is 25 stitches per centimeter and the stitch spacing is 1.8 mm.
[0083] Comparative Example 3: Canceling the application of silicone coating Differences from Example 3 In comparative example 3, the step of coating the silicone coating was omitted and laser processing was performed directly. This design was used to verify the effect of the silicone coating in the edge smoothing process of laser processing.
[0084] Preparation process Microfiber cloth substrate preparation: The matrix was prepared in full accordance with the formulation and process of Example 1.
[0085] Laser Processing: Preprocessing: Use ultraviolet laser with wavelength of 355nm and power of 0.7W / cm 2 , scanning speed 260mm / s; Material Removal: Use green laser with wavelength of 532nm and power of 1.8W / cm 2 , focus diameter 150 microns, scanning speed 140mm / s.
[0086] Embroidery craft: Use three-strand twisted polyester embroidery thread; The embroidery density is 30 stitches per centimeter and the stitch spacing is 1.5 mm.
[0087] Comparative Example 4: Flexibility Enhancer Not Optimized Differences from Example 4 In comparative example 4, the addition ratio of the flexibility enhancer is fixed at 3 wt.%, and the ratio of the flexibility enhancer to the plasticizer is not adjusted. This design is used to compare the effects of the optimization of the flexibility enhancer and the plasticizer on the flexibility of the substrate and the stability of the combination of the embroidery layer.
[0088] Preparation process Microfiber cloth substrate preparation: Prepare a waterborne polyurethane composition, the components are as follows: Waterborne polyurethane: 60wt.%; Flexibility enhancer: 3wt.%; Plasticizer: 5wt.%; Photosensitizer: 2wt.%; Curing accelerator: 1wt.%; Solvent: 29wt.%.
[0089] The microfiber cloth substrate was prepared according to the impregnation and drying process of Example 1.
[0090] Applying silicone coating: The coating thickness is 30 μm and the coating composition is the same as that in Example 4.
[0091] Laser Processing: The laser processing parameters are the same as those in Example 1.
[0092] Embroidery craft: The embroidery density is 20 stitches per centimeter and the stitch spacing is 2 mm.
[0093] Comparative Example Summary Comparative Example 1 (no photosensitizer added): verify the effect of photosensitizer on the control of laser processing edge decomposition path.
[0094] Comparative Example 2 (without cooling airflow): Verify the effect of cooling airflow on heat accumulation and edge smoothing during laser processing.
[0095] Comparative Example 3 (canceling the silicone coating): verifying the effect of the silicone coating on edge protection during laser processing.
[0096] Comparative Example 4 (flexibility enhancer not optimized): verify the effect of the ratio of flexibility enhancer to plasticizer on the flexibility of the substrate and the bonding stability of the embroidery layer.
[0097] Experiment 1: Laser processing edge smoothness test Experiment purpose: to verify the effects of photosensitizer, silicone coating and cooling airflow on the edge smoothness of the hollow area, and to evaluate the difference in effect between the embodiment and the comparative example in laser processing.
[0098] Experimental methods: Experimental samples: Example 1 (photosensitizer + silicone coating + cooling air flow).
[0099] Comparative Example 1 (without photosensitizer).
[0100] Comparative Example 2 (no cooling air flow).
[0101] Comparative Example 3 (no silicone coating).
[0102] Experimental setup: Laser processing conditions: Ultraviolet laser (355nm, power 0.8W / cm 2 , scanning speed 250 mm / s) for pretreatment; Green laser (532nm, power 2W / cm 2 , scanning speed 150 mm / s, focal point diameter 150 microns) is used for material removal; cooling air flow conditions: nitrogen, flow rate 8 L / min, temperature 5°C (except for Comparative Example 2 without cooling air flow).
[0103] Each sample was processed with 10 hollowed-out areas, with an area of 2×2 cm 2 .
[0104] Test method: The burr height and smoothness of the edge of the hollowed-out area were measured using a high-precision laser confocal microscope.
[0105] Each sample was tested 5 times and the average value was calculated.
[0106] Result analysis: By comparing the data of edge smoothness and burr height, the synergistic effect of photosensitizer, cooling airflow and silicone coating in laser processing is verified.
[0107] Experiment 2: Test on the tear resistance of the embroidery layer. Experimental purpose: To evaluate the influence of the strength of polyester embroidery thread and embroidery density on the overall durability of the embroidery layer, and to prove the superiority of the embroidery layer in high-density design.
[0108] Experimental methods: Experimental samples: Embodiment 3 (high-density embroidery, embroidery density 30 stitches / cm, stitch spacing 1.5mm).
[0109] Comparative Example 4 (flexibility enhancer is not optimized, embroidery density is 20 stitches / cm, and stitch spacing is 2 mm).
[0110] Experimental setup: For each sample, select 5×5cm 2 For embroidery area, the test sample quantity is 5 pieces.
[0111] Use an electronic tensile testing machine to clamp the embroidery layer and the edge of the substrate, apply tension to the embroidery layer at a constant speed (10 mm / min), and record the tension value at which the embroidery thread breaks or separates from the substrate.
[0112] Test method: Tensile test range: 0–50N.
[0113] Each sample was tested 3 times and the average value was taken.
[0114] Result analysis: By comparing the tensile values of Example 3 and Comparative Example 4, it is proved that the high-density embroidery design and the optimized flexibility enhancer can improve the durability of the embroidery layer.
[0115] Experiment 3: Edge thermal damage test Experiment purpose: To test the edge thermal damage caused by heat accumulation during laser processing and verify the protective effect of cooling airflow and silicone coating.
[0116] Experimental methods: Experimental samples: Example 2 (cooling air flow + silicone coating).
[0117] Comparative Example 2 (no cooling air flow).
[0118] Comparative Example 3 (no silicone coating).
[0119] Experimental setup: The laser processing conditions were the same as those in Experiment 1.
[0120] The processing area of each sample is 3×3cm 2 hollowed-out area.
[0121] An infrared thermal imager was used to record the temperature distribution and maximum temperature of the hollowed-out edge during laser processing.
[0122] Test method: Infrared thermal imaging analysis software was used to process the thermal images and the average and maximum temperatures of the hollow edge areas were counted.
[0123] After processing, an optical microscope was used to observe the thermal cracks and thermal damage range at the edge.
[0124] Result analysis: By comparing the microscopic observation results of edge thermal damage and temperature distribution data, the protective effect of cooling airflow and silicone coating is proved.
[0125] Experiment 4: Matrix flexibility test Experiment purpose: to verify the effect of the ratio of flexibility enhancer and plasticizer on the flexibility of the matrix, and to prove the superiority of the microfiber cloth of the present invention in terms of flexibility.
[0126] Experimental methods: Experimental samples: Example 4 (flexibility enhancer 5 wt.%, plasticizer 3 wt.%).
[0127] Comparative Example 4 (flexibility enhancer 3 wt.%, plasticizer 5 wt.%).
[0128] Experimental setup: Sample specifications: Cut into 30×30mm rectangular samples with a thickness of 0.5mm.
[0129] The bending test was carried out using a universal material testing machine. Bending stress was applied to the sample at a speed of 5 mm / min, and the minimum force required to bend to 90° was recorded.
[0130] Test method: Five samples of each type were tested, and each sample was tested three times to take the average value.
[0131] Observe whether cracks appear in the substrate during the bending process.
[0132] Result analysis: By comparing the bending force values and crack observation results of the two groups of samples, the optimization effect of the ratio of flexibility enhancer and plasticizer on the flexibility and processing adaptability of the matrix is verified.
[0133] Experiment 5: Test of embroidery three-dimensional effect and visual effect Experiment purpose: To verify the effect of high-density embroidery design on improving three-dimensional effect and aesthetics by comparing the stitch spacing and density of the embroidery layer.
[0134] Experimental methods: Experimental samples: Embodiment 3 (embroidery density 30 stitches / cm, stitch spacing 1.5mm).
[0135] Comparative Example 4 (embroidery density 20 stitches / cm, stitch spacing 2 mm).
[0136] Experimental setup: An embroidery machine was used to form an embroidery area of 50×50 mm on the sample.
[0137] After the embroidery is completed, a 3D scanner is used to measure the three-dimensional height difference of the embroidery area.
[0138] Test method: Analyze the 3D scanning data and count the average height difference and maximum height difference of the embroidery area.
[0139] A 5-person expert panel was used to perform visual scoring, with scoring criteria including three-dimensional perception (40%), detail clarity (30%), and aesthetics (30%).
[0140] Result analysis: The height difference data of embroidery three-dimensional effect and visual scoring results prove that high-density embroidery design can significantly improve the aesthetics of the embroidery layer.
[0141] Summarize Experiments 1 and 3 focus on testing the performance of laser processing, including edge smoothness, thermal damage, etc., reflecting the effects of photosensitizer, silicone coating and cooling airflow.
[0142] Experiments 2 and 4 verified the durability and flexibility of the embroidery layer and the substrate, highlighting the advantages of embroidery density optimization and improved substrate material formulation.
[0143] Experiment 5 focuses on the three-dimensional sense and visual effect of the embroidery layer, demonstrating the practical application value of high-density embroidery design.
[0144] Experiment 1: Laser processing edge smoothness test Experimental Description Purpose Experiment 1 aims to test the smoothness and burr height of the edge of the hollow area of the microfiber cloth after laser processing under different technical schemes (Example 1 and Comparative Examples 1, 2, 3), and evaluate the effects of photosensitizer, cooling airflow and silicone coating on the quality of the hollow edge.
[0145] Experimental procedures Sample preparation: Prepare samples of Example 1 and Comparative Examples 1, 2, and 3, ensuring that the matrix materials of all samples are consistent, with only differences in the conditions of photosensitizer (Comparative Example 1 has no photosensitizer), siloxane coating (Comparative Example 3 has no coating) and cooling airflow (Comparative Example 2 has no cooling airflow).
[0146] The size of each set of samples is 5×5cm, ensuring that the design size of the hollow area is uniformly 2×2cm.
[0147] Laser Processing: The laser equipment uses dual-wavelength laser (355nm ultraviolet + 532nm green light).
[0148] Processing parameters: UV laser for photochemical pretreatment: power 0.8W / cm 2, scanning speed 250mm / s; Green laser for material removal: power 2W / cm 2 , focus diameter 150 microns, scanning speed 150mm / s.
[0149] Cooling conditions: The nitrogen cooling flow rate was 8 L / min and the temperature was 5° C. (only Comparative Example 2 had no cooling flow).
[0150] Edge Testing: A laser confocal microscope was used to perform three-dimensional scanning of the hollow edge to measure the burr height (unit: micrometer) and edge smoothness (smoothness value range 0-1, 1 is completely smooth and 0 is completely rough).
[0151] Ten hollow areas were processed for each group of samples, and each hollow area was measured 5 times to take the average value.
[0152] Experimental data Table name: Laser processing edge smoothness and burr height test data Experimental Summary Through the test of Example 1 and Comparative Examples 1, 2, and 3, this experiment found that the photosensitizer, cooling airflow, and silicone coating had a significant effect on the smoothness and burr height of the edge of the hollowed-out area. Example 1 had the lowest burr height (about 3 microns on average) and the highest smoothness value (close to 0.89), reflecting the synergistic effect of the various elements in the technical solution of the present invention. Comparative Example 1 has no photosensitizer, and the laser processing lacks a photochemical decomposition mechanism, resulting in a random thermal decomposition path of the material and a large number of burrs (about 7.4 microns on average), which verifies the important role of photosensitizer in controlling the laser decomposition path.
[0153] In Comparative Example 2, since no cooling airflow was used during the laser processing, the heat accumulation effect was significant, and obvious overheating occurred at the hollow edge, with the highest burr height (average of about 12 microns) and the worst smoothness value (about 0.45). This shows that the cooling airflow can effectively suppress heat accumulation in laser processing and reduce edge thermal damage. In addition, the siloxane coating was cancelled in Comparative Example 3. Although the photosensitizer and cooling airflow were still used, the edge decomposed unevenly due to the lack of physical protection of the coating, the burr height was about 5.4 microns, and the smoothness value was 0.69, indicating that the siloxane coating has a significant protective effect in laser processing.
[0154] Based on the experimental results, it can be deduced that the photosensitizer guides the decomposition path of the laser through a photochemical mechanism, the cooling airflow reduces thermal damage through heat transfer, and the siloxane coating achieves edge smoothing by providing edge melting protection. These mechanisms work synergistically, and ultimately make the processing effect of Example 1 in the hollow area far better than the control example. Through such verification, the technical solution of the present invention not only optimizes the laser processing performance, but also solves the problems of many burrs and poor edge quality in the hollow area in the prior art, and has significant innovation and practicality.
[0155] Experiment 2: Test on the tear resistance of the embroidery layer Experimental Description Purpose The purpose of this experiment is to test the tear resistance of the embroidery layer under different embroidery densities and substrate flexibility, evaluate the technical differences between Example 3 and Comparative Example 4, and verify the role of high-density embroidery design and flexibility enhancer optimization in improving the stability and tensile strength of the embroidery layer.
[0156] Experimental procedures Experimental sample preparation Example 3: A high-density embroidery design is adopted, the embroidery density is 30 stitches per centimeter, the stitch spacing is 1.5 mm, the polyester embroidery thread is three-strand twisted filaments (diameter 15 microns, tensile strength 280 MPa), and the matrix flexibility enhancer content is 5wt.%.
[0157] Comparative Example 4: A lower embroidery density was adopted, the embroidery density was 20 stitches per centimeter, the stitch spacing was 2 mm, the polyester embroidery thread was three-strand twisted filaments (diameter 17 microns, tensile strength 240 MPa), and the matrix flexibility enhancer content was 3 wt.%.
[0158] Five samples were prepared for each group, and the size of the embroidery area was uniformly 5×5 cm.
[0159] Tensile test Test equipment: Electronic tensile testing machine, tensile range 0–50N, clamp spacing 30mm.
[0160] Test method: Clamp the embroidery area in the tensile testing machine fixture; Apply tension to the embroidery layer at a constant tensile speed of 10 mm / min, and record the tension value at which the embroidery thread breaks or separates from the substrate; test each sample 3 times and take the average value.
[0161] Data Recording The maximum pulling force of the embroidery layer and the separation position of the embroidery layer from the substrate were recorded.
[0162] Experimental data Table name: Test data of embroidery layer's tear resistance performance Experimental Summary This experiment tested the tensile resistance of the embroidery layer of Example 3 and Comparative Example 4, and found that the high-density embroidery design and optimized substrate flexibility significantly improved the tensile resistance of the embroidery layer. The maximum tensile force of Example 3 was 43N on average, which was about 48% higher than 29N of Comparative Example 4. This shows that the high-density embroidery layer not only enhances the bonding force between the embroidery and the substrate, but also effectively disperses the tensile stress, making the embroidery layer less likely to fall off or break under high tension.
[0163] From a mechanism analysis, the high-density embroidery design (embroidery density 30 stitches / cm) increases the bonding area between the polyester embroidery thread and the microfiber cloth substrate through a tighter stitch distribution and a smaller stitch spacing (1.5mm), while reducing the tensile stress borne by a single stitch, making the overall embroidery layer more stable and resistant to damage under external forces. Comparative Example 4 uses a low-density design (20 stitches / cm, stitch spacing 2mm), with a smaller bonding area, and the tensile force is concentrated on fewer stitches, making the embroidery layer more susceptible to local damage or detachment.
[0164] In addition, the optimized ratio of the flexibility enhancer (5wt.%) further improves the toughness of the substrate, allowing it to share part of the stress when the embroidery layer is stretched, avoiding the substrate from breaking or delaminating. In contrast, the flexibility enhancer content in Comparative Example 4 is low (3wt.%), and the substrate is not flexible enough, which makes the interface between the embroidery layer and the substrate easy to peel off, thereby reducing the overall tensile resistance. This further verifies the synergistic optimization effect of substrate flexibility and embroidery design.
[0165] Combining the experimental results and mechanism analysis, this experiment fully demonstrates the key contribution of high-density embroidery design and optimization of flexibility enhancers to improving the durability of the embroidery layer. It also solves the problem of easy detachment and breakage of the embroidery layer in the existing technology, and provides technical guarantee for microfiber cloth embroidery in high-intensity usage scenarios.
[0166] Experiment 3: Edge thermal damage test Experimental Description Purpose The purpose of this experiment is to test the degree of thermal damage to the hollow edge during laser processing under different cooling airflow and coating conditions, evaluate the difference in effect between Example 2 and Comparative Examples 2 and 3, and verify the key role of cooling airflow and silicone coating in reducing heat accumulation and protecting edge quality.
[0167] Experimental procedures Sample preparation Example 2: comprises a cooling gas flow (nitrogen, 8 L / min, temperature 5°C) and a siloxane coating (thickness 35 microns, containing 10 wt.% silicon oxide powder).
[0168] Comparative Example 2: No cooling airflow treatment, only the silicone coating is retained.
[0169] Comparative Example 3: No silicone coating, only cooling air flow (nitrogen, 8 L / min, temperature 5° C.) was retained.
[0170] Five samples were prepared for each group, with a sample size of 5×5 cm and a laser-processed hollow area of 3×3 cm.
[0171] Laser Processing Laser equipment: dual-wavelength laser (355nm ultraviolet + 532nm green light).
[0172] Processing parameters: UV laser: power 0.7W / cm 2 , scanning speed 260mm / s; Green laser: power 2W / cm 2 , focus diameter 150 microns, scanning speed 140mm / s.
[0173] Cooling conditions: Example 2 and Comparative Example 3 used nitrogen cooling with a flow rate of 8 L / min and a temperature of 5°C; Comparative Example 2 has no cooling airflow.
[0174] Test Method An infrared thermal imager was used to record in real time the maximum temperature and thermal damage distribution of the hollowed-out edge during laser processing. After laser processing, an optical microscope was used to observe the thermal damage of the edge (such as cracks, carbonization range, etc.). Each sample was measured 3 times, and the temperature value and thermal damage area were recorded.
[0175] Experimental data Table name: Laser processing edge thermal damage test data Experimental Summary The experimental results show that Example 2 performs best in controlling the thermal damage of the hollow edge, with the maximum temperature kept below 150°C and the average thermal damage area being only 1.6 mm. 2 , significantly better than comparative example 2 (average temperature 218°C, thermal damage area 6.6mm 2 ) and Comparative Example 3 (average temperature 178°C, thermal damage area 4.0 mm 2). This indicates that the cooling airflow and the silicone coating have a synergistic effect in suppressing heat accumulation and reducing edge thermal damage, and the lack of either one will significantly reduce the processing quality.
[0176] The introduction of cooling airflow plays a key role in suppressing heat accumulation during laser processing. The experiment found that in Comparative Example 2, due to the lack of cooling airflow, the temperature of the laser action area rose rapidly to 220°C, and obvious carbonization and cracks appeared on the edge. However, in Example 2, under nitrogen cooling (5°C, 8L / min), the processing temperature was significantly reduced, avoiding the spread of thermal damage. This result verifies that the cooling airflow effectively removes the laser heat through thermal convection, thereby suppressing the edge structure damage caused by high temperature.
[0177] The protective effect of the siloxane coating was also verified in the experiment. Although cooling airflow was used in Comparative Example 3, due to the lack of coating protection, the laser acted directly on the substrate material, resulting in uneven distribution of heat energy and local carbonization on the edge (the average thermal damage area was 4.0 mm 2 ). In contrast, the introduction of the siloxane coating in Example 2 effectively disperses the laser heat energy through melting, while forming a protective barrier to prevent direct damage to the substrate by the laser. This result is consistent with the mechanism analysis, that is, the thermal conductive filler (silicon oxide powder) in the coating disperses the local heat evenly to a larger area by enhancing the thermal conductivity of the coating, thereby reducing the risk of thermal damage to the edge.
[0178] Experiment 4: Matrix flexibility test Experimental Description Purpose The purpose of this experiment is to test the effect of the ratio of flexibility enhancer to plasticizer on the flexibility of the microfiber cloth substrate, evaluate the difference between Example 4 and Comparative Example 4, and verify the role of flexibility enhancer optimization in improving the flexibility and bending resistance of the substrate.
[0179] Experimental procedures Sample preparation Example 4: The content of the flexibility enhancer is 5wt.%, the content of the plasticizer is 3wt.%, and the optimized aqueous polyurethane composition is used to prepare a microfiber cloth substrate. The sample size is 30×30mm and the thickness is 0.5mm.
[0180] Comparative Example 4: The content of the flexibility enhancer is 3 wt.%, the content of the plasticizer is 5 wt.%, and other formulas are the same as those in Example 4, and the sample specifications are consistent with those in Example 4.
[0181] Five samples were prepared for each group.
[0182] Experimental setup and test conditions Test equipment: Universal material testing machine, loading range 0–50N.
[0183] Test conditions: The sample was fixed on the bending fixture, and the fixture spacing was set to 30 mm; Apply bending stress at a speed of 5 mm / min until the bending angle reaches 90°, and record the minimum force required (N); At the same time, observe whether the sample has cracks during the bending process.
[0184] Data Recording Each sample was subjected to three bending tests, the minimum force value was recorded, and the occurrence of cracks was counted.
[0185] Experimental data Sample No. Flexibility enhancer (wt.%) Plasticizer (wt.%) Bending force(N) Crack situation Example 4-1 5 3 16.4 No cracks Example 4-2 5 3 15.8 No cracks Example 4-3 5 3 17.1 No cracks Example 4-4 5 3 16.0 No cracks Embodiment 4-5 5 3 16.6 No cracks Comparative Example 4-1 3 5 23.2 Obvious cracks Comparative Example 4-2 3 5 22.7 Slight crack Comparative Example 4-3 3 5 23.8 Obvious cracks Comparative Example 4-4 3 5 22.9 Obvious cracks Comparative Examples 4-5 3 5 23.5 Obvious cracks Table name: Matrix flexibility bending force value and crack test data Experimental Summary The experimental results show that Example 4 has a significant advantage in substrate flexibility, with an average minimum force of 16.38 N required to bend to 90°, and no cracks were observed during the bending process. This is in sharp contrast to the results of Comparative Example 4, where the average bending force was 23.22 N and cracks appeared in many places on the sample, indicating that the optimized ratio of the flexibility enhancer and plasticizer significantly affects the flexibility and crack resistance of the substrate.
[0186] From a mechanistic analysis, the flexibility enhancer (such as polydimethylsiloxane) introduces highly flexible molecular segments into the waterborne polyurethane matrix, so that the matrix has a higher degree of freedom of molecular chains when subjected to bending or tensile stress, thereby achieving uniform dispersion of stress and improving the crack resistance of the matrix. In Example 4, the flexibility enhancer content is 5wt.%, which significantly improves the toughness of the matrix. At the same time, with 3wt.% of plasticizer, while maintaining the softness of the material, it avoids the phenomenon that the matrix is too loose or the mechanical strength decreases due to an excessively high plasticizer ratio. In Comparative Example 4, the flexibility enhancer content is low (3wt.%) and the plasticizer ratio is high (5wt.%). Although a certain degree of softness is improved, the excessive amount of plasticizer leads to a loose matrix structure and lacks sufficient crack resistance.
[0187] The experiment also found that the sample of Example 4 showed a lower bending force value in the bending test, indicating that the optimized formula is more adaptable to complex processing conditions or dynamic usage scenarios, especially in the case of multiple punctures or bending in the embroidery process, which can effectively avoid matrix rupture or delamination. The sample of Comparative Example 4 had frequent cracks and a significantly higher bending force value, indicating that it is insufficiently adaptable to dynamic processing environments.
[0188] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A microfiber cloth embroidery and its preparation process, characterized in that: Includes the following structures: A microfiber cloth substrate, wherein the microfiber cloth substrate is made of a microfiber mesh cloth impregnated with an aqueous polyurethane composition; A laser hollowed-out area, wherein the laser hollowed-out area is formed by laser processing, and the edge of the hollowed-out area is smoothed by laser processing; The embroidery layer is arranged in the laser hollowed-out area and is sewn with polyester embroidery thread.
2. The microfiber cloth embroidery and the preparation process thereof according to claim 1, characterized in that: The aqueous polyurethane composition comprises the following components: 55-65 wt.% of waterborne polyurethane, wherein the waterborne polyurethane is prepared by reacting polyether polyol, aromatic polyisocyanate and chain extender; 1-3 wt.% of photosensitizer, wherein the photosensitizer is selected from imide compounds or ultraviolet light initiators; 2 to 5 wt.% of a flexibility enhancer, wherein the flexibility enhancer is polydimethylsiloxane; 3 to 6 wt.% of plasticizer, wherein the plasticizer is a citrate or a phthalate; 0.5-2 wt.% of a curing accelerator, wherein the curing accelerator is an organic tin catalyst or an amine catalyst; The solvent is 20-30 wt.%, and the solvent is a mixture of deionized water and isopropanol.
3. The microfiber cloth embroidery and the preparation process thereof according to claim 1, characterized in that: The polyester embroidery thread of the embroidery layer is formed by twisting three filaments, each filament has a diameter of 10 to 20 microns, and the tensile strength of a single polyester embroidery thread is 200 to 300 MPa.
4. The microfiber cloth embroidery and the preparation process thereof according to claim 1, characterized in that: The edge of the laser hollowed-out area is formed by auxiliary processing with a siloxane coating, the thickness of the siloxane coating is 30 to 50 microns, and the coating further comprises a thermally conductive filler, which is aluminum oxide powder or silicon oxide powder, and the particle size of the thermally conductive filler is 0.5 to 1.5 microns, and the mass fraction is 10 to 15 wt.%.
5. A preparation process of microfiber cloth embroidery, applied to the microfiber cloth embroidery according to claims 1 to 4, characterized in that: A preparation process of microfiber cloth embroidery, characterized in that it comprises the following steps: Preparation of microfiber cloth substrate: impregnating microfiber mesh cloth into an aqueous polyurethane composition and drying to form a microfiber cloth substrate; Applying coating: applying a silicone coating on the surface of the microfiber cloth substrate; Laser processing: forming a hollow area on the microfiber cloth substrate by laser processing; Embroidery technology: a polyester embroidery thread embroidery layer is arranged in the hollow area, wherein the embroidery density is 15 to 30 stitches per centimeter.
6. The preparation process of microfiber cloth embroidery according to claim 5, characterized in that: The waterborne polyurethane composition has an immersion temperature of 30-40° C., an immersion time of 3-5 minutes, a drying temperature of 60-80° C., a drying time of 30-60 minutes, and an immersion method of static immersion or cyclic immersion.
7. The preparation process of microfiber cloth embroidery according to claim 5, characterized in that: The siloxane coating is applied by spraying or roller coating, and after coating, it is cured at 60-100° C. for 20-40 minutes. An adhesion enhancer is added to the coating, and the adhesion enhancer is an acrylate copolymer, and its content is 3-5 wt.% of the total mass of the coating.
8. The preparation process of microfiber cloth embroidery according to claim 5, characterized in that: The laser processing comprises the following steps: The hollowed-out area was photochemically pretreated using an ultraviolet laser with a wavelength of 355 nm, a laser power of 0.5 to 1.0 W / cm², and a scanning speed of 200 to 300 mm / s. The hollowed-out area is removed using a green laser with a wavelength of 532 nm, a laser power of 1.5 to 2.5 W / cm², a scanning speed of 100 to 200 mm / s, and a focal diameter controlled within the range of 100 to 200 microns.
9. The preparation process of microfiber cloth embroidery according to claim 5, characterized in that: The embroidery process uses polyester embroidery thread to sew in a single needle cycle mode, the stitch spacing is 1.5 to 2.5 mm, and the minimum distance between the embroidery thread and the hollow edge of the microfiber cloth is 0.3 to 0.5 mm.
10. The preparation process of microfiber cloth embroidery according to claim 5, characterized in that: During the laser processing, a cooling air flow of 5 to 10 L / min is introduced simultaneously. The cooling medium is nitrogen or carbon dioxide air flow, and the cooling air flow temperature is controlled between -5°C and 10°C.